DESAIN KEMASAN COKELAT GARUT PACKAGING DESIGN OF GARUT CHOCOLATE (Kajian Visual Estetik pada Kemasan Chocodot Perusahaan Tama Chocolate Garut) (Visual Aesthetics Study on Chocodot Packaging at Tama Chocolate Company Garut) - Shelly Pratiwi; Harry Sulastianto (Universitas Pendidikan Indonesia (UPI), 2013)
ABSTRACTChocodot Chocolate is one of the special products in Garut, West Java, which proved to be superior in market. Because the company was paying attention in quality of taste and they was very concerned in uniqueness of the packaging, Especially Chocodot chocolate ‘Up to Date’ edition. As a pioneer of chocolates with attractive design packaging and unique names of product, it was interesting to research especially in visual aesthetics well about typography, style or realization of illustration, and composition/layout in packaging form design based on theory of design. This paper use descriptive research method with qualitative approaches and using literary review, observation, and interview in collection technique.Based on the results of research, it can be conclude that the typography used was dominated by typeface of Sans Serif which focused on readability. Cartoon, realistic, and decorative were used in the illustration style, especially on the package icon, which is customized by the name of the product and inspired by the condition of society now day. Point of interest composition/layout in the package of ‘Up to Date’ edition focused on the name of the product, or the product icon, even on both. The unification of them on the packaging showed similarity with healthcare or pharmaceutical products, because of using white colour as the background which used in packaging pharmaceutical products. Key Words: Packaging Design, Chocodot Up to Date Edition, Typography, Illustration, Composition/Layout. ABSTRAKCokelat Chocodot merupakan salah satu produk khas Kabupaten Garut, Jawa Barat yang terbukti unggul di pasaran. Karena selain memperhatikan kualitas rasa, perusahaan juga sangat memperhatikan keunikan dari kemasannya, salah satunya yaitu cokelat Chocodot edisi cokelat Up to Date. Sebagai pelopor cokelat dengan desain kemasan menarik dan nama produk yang unik, sangat menarik untuk diteliti khususnya mengkaji visual estetika baik mengenai tipografi, gaya atau perwujudan gambar ilustrasi, dan komposisi/layout dari bentuk desain kemasan ini berdasarkan teori desain. Metode penelitian deskriptif dengan pendekatan kualitatif digunakan dalam penelitian ini, serta dengan teknik pengumpulan studi pustaka, observasi, dan wawancara/interview. Berdasarkan hasil penelitian dapat disimpulkan bahwa tipografi yang digunakan didominasi oleh jenis huruf Sans Serif yang berorientasi pada kemudahan untuk dibaca. Gaya ilustrasi kartun, realis, dan dekoratif digunakan dalam ilustrasi khususnya pada ikon kemasan, yang disesuaikan dengan nama produk dan terinspirasi dari keadaan masyarakat sekarang. Point of interest komposisi/layout kemasan edisi Up to Date terfokus pada bagian nama produk, atau ikon produk, bahkan pada keduanya. Perpaduan ketiganya pada kemasan memperlihatkan kemiripan produk dengan produk kesehatan atau farmasi, dikarenakan penggunaan putih sebagai latar biasa digunakan untuk kemasan produk farmasi.Kata Kunci: Desain Kemasan, Chocodot edisi Up to Date, Tipografi, Ilustrasi, Komposisi/Layout.